2011
DOI: 10.1161/atvbaha.111.225961
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor (VEGF)-D Stimulates VEGF-A, Stanniocalcin-1, and Neuropilin-2 and Has Potent Angiogenic Effects

Abstract: Objective-The mature form of human vascular endothelial growth factor-D (hVEGF-D ⌬N⌬C) is an efficient angiogenic factor, but its full mechanism of action has remained unclear. We studied the effects of hVEGF-D ⌬N⌬C in endothelial cells using gene array, signaling, cell culture, and in vivo gene transfer techniques. Methods and Results-Concomitant with the angiogenic and proliferative responses, hVEGF-D⌬N⌬C enhanced the phosphorylation of VEGF receptor-2, Akt, and endothelial nitric oxide synthase. Gene arrays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…A role of STC1 in the tumor microenvironment has also been suggested (Yeung et al 2012). This presumption is strengthened by the involvement of STC1 in local inflammation (Sheikh--Hamad 2010) as well as the identification of STC1 as a hypoxia and angiogenic responsive gene (Yeung et al 2005, Law et al 2010, Jauhiainen et al 2011, Roch & Sherwood 2011. To date, biological roles of STC1 in carcinogenesis have been suggested, including cell motility, invasion, and apoptosis (Lai et al 2007, Law et al 2008, Liu et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…A role of STC1 in the tumor microenvironment has also been suggested (Yeung et al 2012). This presumption is strengthened by the involvement of STC1 in local inflammation (Sheikh--Hamad 2010) as well as the identification of STC1 as a hypoxia and angiogenic responsive gene (Yeung et al 2005, Law et al 2010, Jauhiainen et al 2011, Roch & Sherwood 2011. To date, biological roles of STC1 in carcinogenesis have been suggested, including cell motility, invasion, and apoptosis (Lai et al 2007, Law et al 2008, Liu et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…20 Blood flow recovery by Pio-NP was accompanied by arteriogenesis in ischemic hindlimb muscle, which is demonstrated as arterioles with α-smooth muscle actin-positive pericytes. Polymerase chain reaction array revealed that Pio-NP induced multiple genes that are involved in endothelial proliferation and migration (VEGF-A, VEGF-B, VEGF-D, and epidermal growth factor), [21][22][23][24][25][26] as well as vascular smooth muscle cell migration and proliferation (FGF and Gna13). [27][28][29][30] This coordinated induction of endothelial cells and VSMCs is critical for Pio-NP-induced mature arteriogenesis to form functional collaterals.…”
Section: Nagahama Et Al Pioglitazone For Therapeutic Neovascularizatimentioning
confidence: 99%
“…It has been shown that SEMA3B protein competitively binds with NP-1 and inhibits VEGFl65-induced tumor growth by inhibiting tumor angiogenesis and reducing the microvessel density (MVD) [22]. A study also found that the expression of SEMA3B mRNA in lung cancer tissue was negatively correlated with the MVD and the expression of VEGF mRNA [23].…”
Section: Tumor Suppression Of Sema3bmentioning
confidence: 99%